Temperature and Mental Health: Evidence from the Spectrum of Mental Health Outcomes - Jamie Mullins; Corey White (Institute of Labor Economics (IZA), 2019)
This paper characterizes the link between ambient temperatures and a broad set of mental health outcomes. We find that higher temperatures increase emergency department visits for mental illness, suicides, and self-reported days of poor mental health. Specifically, cold temperatures reduce negative mental health outcomes while hot temperatures increase them. Our estimates reveal no evidence of adaptation, instead the temperature relationship is stable across time, baseline climate, air conditioning penetration rates, accessibility of mental health services, and other factors. The character of the results suggests that temperature affects mental health very differently than physical health, and more similarly to other psychological and behavioral outcomes. We provide suggestive evidence for sleep disruption as an active mechanism behind our results and discuss the implications of our findings for the allocation of mental health services and in light of climate change.
Keywords: I10; I12; I18; Q50; Q51; Q54; 330; mental health; weather; climate; suicide; health